The Kinetic Parameters of Carbonaceous Materials Activated with Potassium Hydroxide - Zou Yong; Han Bu-Xing (Adsorption Science & Technology)
On the basis of micropore formation in carbonaceous materials, the activation energy for the potassium hydroxide activation of Chinese petroleum coke and coal has been deduced theoretically as dB 0 /dt = A exp(–E a ∈/RT), where ∈ is the formation energy for the metastable solid formed at the activation temperature. The kinetic parameters (frequency factor, A, and apparent activation energy, E a ) were calculated from this equation as being 5.319 mg/(g min), 36.51 kJ/mol and 6.64 mg/(g min), 49.46 kJ/mol, respectively, for the two carbonaceous materials studied.